COMBINATION OF VESTIBULAR STIMULATION AND PERCEPTUAL MOTOR PROGRAM COULD IMPROVE BALANCE IN CHILDREN WITH FLAT FOOT - Ni Luh Putu Gita Karunia Saraswati; Made Hendra Satria Nugraha; Putu Mulya Kharismawan; Anak Ayu Nyoman Trisna Narta Dewi (Journal of Vocational Health Studies, 2025)
Background: Flat foot is a common lower extremity deformity in children. Underdeveloped arches can lead to complaints such as fatigue during prolonged walking, impaired balance, frequent injuries, and pain. Several interventions can be employed to address these issues, including arch muscle strength exercises, toe curls exercises, calf stretches, and plantar fascia stretches. Purpose: This study aims to prove the effectiveness of a combination of heel raises exercise and vestibular stimulation versus a combination of heel raises exercise and perceptual motor program in increasing lower extremity muscle strength and standing balance in children with flat foot. Method: This research is a quasi-experimental study that utilized a pre-test and post-test two-group design with a purposive sampling method. A total of 30 subjects were put into 2 groups. Group 1 received a combination of heel raise exercises and vestibular stimulation. Group 2 received a combination of heel raise exercise and perceptual motor program. Lower extremity muscle strength was assessed using the Manual Muscle Test (MMT), and standing balance was evaluated using the Pediatric Balance Scale (PBS). Result: Both groups showed differences in the measurement aspects of MMT and PBS (p-value < 0.05). However, no significant difference was found between the groups in the MMT score. In contrast, a significant difference was observed in PBS scores, with Group 2 demonstrating greater improvement (p-value < 0.05). Conclusion: The combination of heel raises exercise and a perceptual motor program is more effective in improving balance in children with flat foot compared to the combination with vestibular stimulation.